ELEVASI DAN TITIK KOORDINAT DALAM PENYUSUNAN JADWAL IMSAKIAH RAMADHAN KANWIL KEMENAG PROVINSI ACEH - ismail, ismail; Ukhti, Laiyina (UIN ALAUDDIN MAKASSAR, 2022)
This article elucidates the utilization of elevation and coordinat point to arrange the imsakiah schedule issued by Regional Office of the Ministry of Religion of Aceh Province. The method used is qualitative with an astronomy approach, this study used the data of imsikiah schedules issued by the Regional Office of the Ministry of Religion of Aceh Province and interview result with compilers. The results of the study can be explained that the elevation data that used to arrange the Imsakiah schedule for the Regional Office of the Ministry of Religion of Aceh Province is fixed, there is no difference elevation data in the highland and lowland. The coordinate point of location that used to arrange the imsakiah schedule are socio-religious coordinates, these coordinates are not correlated with the radius of enforcement location, with the result that the enforcement conversion isunavoidable and the iḥtiyāṭ value is only serves as safety.